Opposing universes in José de Piérola’s El camino de regreso - Vargas Yábar, Miguel (2019)
The novel El camino de regreso (2007) focuses upon the complex nature of Peru’s social structure, where norms and laws operate differently, according to social class, race and origin. The conflictive relationship between the main characters serves as a metaphor for fratricide among fellow countrymen. The armed internal conflict shakes the nation but does not affect all its citizens in the same way. Through fully realized and complex characters, the novel strongly criticizes the structures that made possible the military conflict, but also announces changing times and disruption of the status quo. This essay proposes that what we see in the novel is a change in the social paradigm in which the working classes have been marginalized historically and the ruling classes have traditionally displayed irresponsibility and injustice. El camino de regreso offers a version of a new paradigm that seeks to resolve historically irreconcilable issues, through characters from different social backgrounds who share a common interest in progress, the rule of law, and the protection of the working class majority. The novel gives new meanings to historical events through the experiences of different social actors, inserted within a process of literary truth that demonstrates the author’s concerns regarding the world depicted, and reflects upon the social and cultural upheavals resulting from conflict, while offering a critique of those same upheavals.